Analisis Konflik Tanah dalam Konteks Hukum Adat - Yunita Bernanda; Iis Qomariah; Enggika Mandasari (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
Land conflict is a complex and evolving issue in various regions of Indonesia, particularly in areas that still uphold customary law values. This study aims to analyze the dynamics of land conflict in the context of customary law, focusing on the causes, actors involved, and resolution mechanisms used by indigenous communities. In many cases, conflicts arise due to the overlap between the recognition of indigenous communities’ ulayat rights and government policies that prioritize development and investment interests. This research employs a qualitative approach with case studies in several regions experiencing customary land conflicts, as well as normative juridical analysis of regulations related to the recognition of indigenous communities’ rights. The results show that customary law still holds strong legitimacy among communities, but often lacks adequate legal protection from the state. Therefore, synchronization between state law and customary law is necessary to achieve more just and sustainable land conflict resolution.